Complications after knee derotational osteotomies in patients with anterior knee pain and/or patellofemoral instability: a systematic review with meta-analysis - Inês Figueiredo; Cristina Valente; Ricardo Ribeiro; Bárbara Ferreira; Eluana Gomes; Diego Delgado; Mikel Sánchez; Renato Andrade; João Espregueira-Mendes (EFORT Open Reviews)
Purpose: Investigate intra- and post-operative complications and revisions following distal femoral and/or high tibial derotational osteotomies to correct rotational malalignments of the lower limb in patients with anterior knee pain (AKP) and/or patellofemoral instability (PFI). Methods: A literature search was conducted on PubMed, EMBASE and Web of Science (until 30 September 2023), including studies reporting complications, reinterventions and revisions following knee derotational osteotomies. Incidence rates were collected for each level of derotational osteotomy (distal femur, high tibia or double-level). A meta-analysis using the Freeman–Tukey double arcsine transformation was conducted to estimate the pooled proportions with their 95% confidence intervals (CIs). Results: Twenty-one studies involving 564 osteotomies (n = 484) were included, with a mean follow-up of 45.6 ± 15.7 months. The overall complication proportion was 7.5% (95% CI: 3.9–11.8%). Postoperative residual AKP was seen in a pooled proportion of 7.6% (95% CI: 0.7–18.8%), and persistent PFI was not common (0.1%; 95% CI: 0.0–1.7%). Intraoperative complications occurred in a pooled proportion of 3.8% (95% CI: 2.4–6.0%), with peroneal nerve injury being the most common (1.3%) after derotational high tibial osteotomy. Reintervention was needed in a pooled proportion of 13.0% (95% CI: 2.9–27.2%), primarily for hardware removal (n = 158; 28.3%). There was a pooled proportion of knees requiring revision procedures of 12.3% (95% CI: 2.6–26.1%). Conclusions: Distal femur and high tibial derotational osteotomies exhibit a considerable incidence of intra- and post-operative complications. Peroneal nerve injury, although infrequent, is a significant complication, underscoring the importance of implementing intraoperative preventive measures during derotational high tibial osteotomy.